REVITALIZATION OF TRADITIONAL BALL TOSS GAMES TO ENHANCE COOPERATION AND COMMUNICATION AMONG EARLY CHILDHOOD CHILDREN - Muttaqin, Muhammad’Azam; Arisanti, Fifi (Media Inovasi Pendidikan dan Publikasi, 2025)
Traditional games are increasingly overshadowed by the advancement of modern technology, making their revitalization essential to preserve cultural values while supporting the social development of early childhood children. This article aims to explore the role of the traditional ball toss game as a medium for enhancing cooperation and communication among early childhood children. The primary focus of this study is how the game can be utilized as an effective learning strategy in both formal and informal educational settings. The research employs a descriptive qualitative approach, involving participant observation of 20 children aged 5–6 years who participated in the ball toss game within a community playground setting. In-depth interviews were conducted with educators and parents to understand the impact of the game on children's social development. The data were analyzed thematically to identify patterns of interaction and communication that emerged during the activities.The findings reveal that the ball toss game encourages children to work collaboratively in groups, develop verbal and non-verbal communication skills, and strengthen social bonds among peers. Additionally, the game helps children understand concepts such as roles, rules, and sharing. The implications of this study highlight the importance of integrating traditional games into early childhood education curricula as a learning medium that supports social and emotional development. This research makes a significant contribution to culturally relevant and sustainable learning strategies.